Analisis Minat Pemuda Untuk Beternak Itik Di Kecamatan Hamparan Rawang Kota Sungai Penuh - Gea Riski Pasarela; Afriani Harahap; Indra Sulaksana (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the interest of young people in raising ducks and determine the factors that influence it. The method used in this study is a survey method using primary data with data collection techniques through observation, interviews, and distributing questionnaires to 52 respondents consisting of young people who raise livestock, young people whose parents raise livestock, young people who do not raise livestock, and young people who no longer raise livestock. While secondary data was obtained from the Central Statistics Agency (BPS) of Sungai Penuh City, the Livestock and Fisheries Service of Sungai Penuh City. The data were analyzed using multiple linear regression analysis to identify the influence of each variable on the interest in raising ducks. The results showed that the interest of young people in raising ducks based on indicators stating interest, real interest, tested interest, and invored interest was in the category of quite interested with an average value of 58.39%. The results of the determination coefficient test R2 (0.871), showed that 87.1% was influenced by factors of land ownership, income, number of family members and opportunities to obtain information. The results of the F test show that all independent variables simultaneously have a significant effect on youth interest (Sig 0.000 < 0.05) and the T test shows that the variables of income and opportunity to obtain information and youth status (dummy) have a significant effect on youth interest. Based on the results of the study, it can be concluded that the interest of youth in raising ducks in Hamparan Rawang District is in the category of quite interested and is influenced by income, opportunity to obtain information, and youth status.